Wetting length in gas metal arc brazing of galvanised steel. (17th February 2017) - Makwana, P.; Shome, M.; Goecke, S.-F.; De, A.
Abstract : Appropriate substrate surface wetting by a molten filler ensures a sound bead profile during brazing. A theory to estimate the wetting length considering gradual cooling of liquid filler and loss in its ability to spread is currently unavailable. We present here a methodology to estimate wetting length based on the minimisation of energy for spreading of a liquid filler considering its gradual cooling and tested the computed results in gas metal arc brazing of galvanised sheets for a wide range of conditions. The computed wetting lengths are used further to estimate bead height and toe angle of joint profile. GRAPHICAL ABSTRACT: